THE INDIVIDUAL-PSYCHOLOGICAL PECULIARITIES OF MOTORIC COMPONENTS OF THE MNEMIC PROCESSING OF INFORMATION BY PILOT-CADETS - Volkov, D.; Kravchenko, K.; Bilichenko, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
Unlike many other professions the activity of pilots is conducted under conditions of pretty high risks to perish because of accidents, malfunctions and catastrophes. Throughout the history of development of aviation, the overwhelming amount of accidents and catastrophes has been connected with the constructive peculiarities of hardware, malfunctions of equipment and the unreliability of flying devices. Currently, despite the significant process in terms of perfection of aviation hardware, aimed at the increase of reliability of its exploitation, there’s a permanent increase in human victims and increase in material losses as a result of accidents and catastrophes. This eventually leads to the fact that specialists address more and more not the issue of technical reliability of the flying device, but more about the role of the human factor in terms of security while piloting, and in this regard special interest is demonstrated to a number of issues that are related to the individual-psychological peculiarities of behavior under extreme conditions when performing pilot activities.The article presents the results of an empirical research, that is conducted on the basis of the Kharkiv Ivan Kozhedub national Air Force university, The Military Institute of the Kyiv Taras Shevchenko University and the The Dniepropetrovks National Oles Honchar University. The empirical research has been conducted with the following: an experimental group – of 32 cadets – pilots of the third and the fourth courses, a control group that consisted of cadets from the fourth course (50 individuals) and students of the fourth course (50 individuals).In order to conduct that necessary research a number of psycho diagnosis approaches have been selected: the testquestionnaire G. Ajzenka EPI, adapted by A. Schmelevij; the Diagnosis questionnaire “Human-machine”; the approach of conducting express diagnosis of the peculiarities of the nervesystem based on the psychmotorical indicators E, Ilina (tepingtest); the psychomotoric test “Zero” E, Ilina, adopted by D. Volkov.
Keywords: individual typological characteristics, mnemonic information processing, cadet pilots